PENGARUH DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT NUTECH INTEGRASI JAKARTA SELATAN - Rahmawati, Dini; Indirasari, Indri (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
The purpose of this study is to determine the influence of discipline and work motivation on employee performance at PT Nutech Integrasi Jakarta Selatan, both partially and simultaneously. This research employs a quantitative approach. The population consists of 150 employees of PT Nutech Integrasi Jakarta Selatan. The sampling technique used in this study is Slovin’s formula, resulting in a sample size of 110 employees from the same company. The results of the analysis show that discipline and work motivation have a significant effect on employee performance, as indicated by an adjusted R square value of 0.812, which means that 81.2% of employee performance is influenced by these two variables, while the remaining 18.8% is affected by other factors not examined in this study. Based on the t-test, the discipline variable has a partial effect on employee performance, as shown by tcount > ttable (20.899 > 1.982) with a significance value of 0.000 < 0.05. Likewise, the work motivation variable also shows a partial effect, with tcount > ttable (7.725 > 1.982) and a significance value of 0.000 < 0.05. Furthermore, the F-test results indicate that discipline and work motivation have a simultaneous influence on employee performance, proven by Fcount > Ftable (231.733 > 3.08) and a significance value of 0.000 < 0.05. Therefore, it can be concluded that both discipline and work motivation significantly and simultaneously affect employee performance at PT Nutech Integrasi Jakarta Selatan Keywords: Dicipline, Work Motivation, Employee Performance